PENGARUH PENAWARAN TENAGA KERJA, PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP UPAH MINIMUM PROVINSI INDONESIA - Ade Indah Puspa Darma; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The study aims to analyzed the effect of labor suply, economic growth and inflation on Indonesian provincial minimum wage. Data used from 2016-2018 that involve 34 provinces in Indonesia by The Central Bureau of Statistics. The data analysis used regression panel model to estimate the effect of dependent variabels to Indonesian provincial minimum wage. The result of the study showed that: 1) The Labor Supply did not affected Indonesian provincial minimum wage, 2) The economic growth has positive and singificant effect to Indonesian provincial minimum wage, 3) Infaltion has positive effect and not significant to Indonesian provincial mimimum wage.